2015
DOI: 10.1097/sla.0000000000001488
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Versus Open Surgery for Gastric Gastrointestinal Stromal Tumors

Abstract: Laparoscopic resection for gGISTs is associated with favorable short-term outcomes without compromising oncologic results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(28 citation statements)
references
References 24 publications
1
26
0
1
Order By: Relevance
“…No significant difference in postoperative complications was observed between the LR and OR groups in the present study, which is consistent with the findings of other studies[31,32]. Some other studies have shown that LR of gGISTs may reduce postoperative complications[33]. The Clavien-Dindo classification is a commonly used evaluation system for postoperative complications[17].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…No significant difference in postoperative complications was observed between the LR and OR groups in the present study, which is consistent with the findings of other studies[31,32]. Some other studies have shown that LR of gGISTs may reduce postoperative complications[33]. The Clavien-Dindo classification is a commonly used evaluation system for postoperative complications[17].…”
Section: Discussionsupporting
confidence: 91%
“…Some other studies have obtained different results. A European multicenter study of 61 centers involving 1413 patients with gGISTs revealed that the 5-year DFS rate in the LR group was significantly higher than that in the OR group[33]. In another meta-analysis, the recurrence rate in the OR group was significantly higher than that in the LR group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various clinical studies and meta-analysis have demonstrated that LAP for GISTs of the stomach had associated with lesser pain, shorter hospital stay, faster postoperative recovery, lower morbidity, and similar recurrence rates compared to open approach (OPEN). [4567] However, there is a paucity in the literature on the management and outcomes of laparoscopic small bowel GISTs resection due to relatively low incidence rate. [8] Therefore, the reliable short-term outcomes following LAP for small bowel GISTs are unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Complete resection, together with tumor-free margins and avoidance of tumor rupture, remain the only curative treatment option for resectable GISTs, because tumor rupture, either spontaneous or at surgery, is associated with a high risk of recurrence [3,4]. Unfortunately, approximately two thirds of patients with GIST will experience recurrence or metastasis during the course of their disease [5,6,7]. Tumor size and mitotic count are well-documented prognostic factors in resectable GISTs, but additional factors - particularly tumor rupture and tumor site - seem to modify the risk, as shown in the National Institutes of Health (NIH) consensus classification system based on large GIST cohorts [8].…”
Section: Introductionmentioning
confidence: 99%